THE EFFECT OF JOB STRESS, JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON PERFORMANCE - Yanner, Yanner; Bernarto, Innocentius; Wuisan, Dewi (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract. This study aims to examine the negative effect of job stress on organizational commitment; positive effect of job satisfaction on organizational commitment; negative effect of job stress on performance; positive effect of job satisfaction on performance; positive effect of organizational commitment on performance. The target population were all 45 JBP High School teachers. The sampling technique used was saturated or census samples. The data was collected through a questionnaire and analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) approach using SmartPLS program. The results showed that the job stress negatively affected organizational commitment and performance. In addition, the organizational commitment and job satisfaction had a positive effect on performance.Keywords: Job Stress, Job Satisfaction, Organizational Commitment, Performance Abstrak. Penelitian ini bertujuan untuk menguji efek negatif dari stres kerja pada komitmen organisasi; pengaruh positif kepuasan kerja terhadap komitmen organisasi; efek negatif dari stres kerja pada kinerja; efek positif kepuasan kerja terhadap kinerja; efek positif dari komitmen organisasi terhadap kinerja. Populasi target adalah semua 45 guru SMA JBP. Teknik pengambilan sampel yang digunakan adalah sampel jenuh atau sensus. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan pendekatan Partial Least Squares - Structural Equation Modeling (PLS-SEM) menggunakan program SmartPLS. Hasil penelitian menunjukkan bahwa stres kerja berpengaruh negatif terhadap komitmen dan kinerja organisasi. Selain itu, komitmen organisasi dan kepuasan kerja berpengaruh positif terhadap kinerja.Kata Kunci: Stres Kerja, Kepuasan Kerja, Komitmen Organisasi, Performa